Given
"y' + \\frac{1-3x^2}{x(1-x^2)} y =\\frac{1} {1-x^2}"
This is a linear equation with
"p(x)=\\frac{1-3x^2}{x(1-x^2)},\\ \\ \\ q(x) =\\frac{1} {1-x^2}"
Since
"\\begin{aligned}\n\\frac{1-3x^2}{x(1-x^2)}&=\\frac{A}{x }+\\frac{B}{1-x}+\\frac{C}{1+x}\\\\\n&= \\frac{A (1-x^2)+Bx(1+x)+Cx(1-x)}{x(1-x^2)}\\\\\n1-3x^2&=A (1-x^2)+Bx(1+x)+Cx(1-x)\n\\end{aligned}"
Then
"\\begin{aligned}\n\\text{At } \\ x&=0\\ \\ \\ \\to \\ A=1\\\\\n \\text{At } \\ x&=-1\\ \\ \\ \\to \\ C=1\\\\\n \\text{At } \\ x&= 1\\ \\ \\ \\to \\ B=-1\n\\end{aligned}"
Hence
"\\begin{aligned}\n\\int p(x)dx&=\\int \\frac{1-3x^2}{x(1-x^2)}dx\\\\\n&=\\int \\frac{dx}{x }-\\int \\frac{dx}{1-x}+\\int \\frac{dx}{1+x}\\\\\n&=\\ln x+\\ln (1-x)+\\ln (1+x)\\\\\n&=\\ln x(1-x^2)\n\\end{aligned}"
Since the integral factor given by
"\\begin{aligned}\n\\mu&=e^{\\int p(x)dx}\\\\\n&=e^{\\ln x(1-x^2)}\\\\\n&= x(1-x^2)\n\\end{aligned}"
Then the solution is
"\\begin{aligned}\n\\mu y&=\\int \\mu q(x)dx\\\\\nx(1-x^2) y &= \\int x(1-x^2)\\frac{1}{1-x^2}dx\\\\\n&=\\int xdx\\\\\n&= \\frac{1}{2}x^2+C\n\\end{aligned}"
Hence
"y= \\frac{ x^2}{2x(1-x^2)}+\\frac{ C }{2x(1-x^2)}"
Comments
Leave a comment